Soil fertility and nutrient uptake of rice influenced by plant growth promoting microbes, seaweed extract and humic acid fortified in situ rice residue compost - Prabhu Vijayakumar; Singaravel Ramaiyan; Ramakichenin Alias Balagandhi Balasubramanian (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Intensive rice cultivation, non-addition of organic matter and indiscriminate use of inorganic fertilizers lead to soil fertility deterioration; on other side, farmers are burning huge quantities of rice residue causing severe air pollution warrants pragmatic disposal solution. In situ composting is considered as a potential alternative to destruction of crop residues. Moreover, fortification of crop residue with beneficial microbes and bio stimulants increase the availability of nutrients which constitutes an integral component in sustainable agriculture.The objective was to evaluate the effect of in situ rice residue compost fortification with PGPM consortia, humic acid and seaweed extract on the soil nutrient availability and uptake by rice. Method The experiment was conducted in a RBD at field condition. Rice was grown under 10 treatments comprising a control (100 % NPK) and nine treatments (in situ rice residue, fortified FYM, fortified in situ rice residue along with 100, 75 and 50 % NPK). Results In situ rice residue fortified with PGPM consortia, humic acid and seaweed extract significantly improved the soil carbon, nutrients' availability (macro and micro) and soil fertility. Combined application of fortified rice residue compost with 75% NPK resulted in significantly higher rice yields (grain 6.03 t ha-1 and straw 8.57 t ha-1) and nutrient uptake. Conclusion In situ rice residue composting provides promising straw disposal method as well as recoups lost share of organic matter and nutrients to soil. Farmers may adapt in situ compost to restore soil health without causing environmental hazard and also sustain crop productivity.